Optical second harmonic generation phase measurement at interfaces of some organic layers with indium tin oxide - Siti Zulaikha Ngah Demon; Miyauchi, Yoshihiro; Mizutani, Goro; Matsushima, Toshinori; Murata, Hideyuki (LCP : journal articles)
Abstract : We observed phase shift in optical second harmonic generation (SHG) from interfaces of indium tin oxide (ITO)/copper phthalocyanine (CuPc) and ITO/pentacene. Phase correction due to Fresnel factors of the sample was taken into account. The phase of SHG electric field at the ITO/pentacene interface, ϕinterface with respect to the phase of SHG of bare substrate ITO was 160°, while the interface of ITO/CuPc had a phase of 140°.